The magnesium-palladium-silver system: Thermodynamic properties of the liquid phase - Dębski A.; Gąsior W.; Gierlotka W.; Baran A.; Polański M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A drop calorimetry method was used to measure the partial and integral mixing enthalpies of Ag-Mg-Pd liquid solutions. The experiments were performed for six separate series of liquid alloys starting from the binary alloys with constant xAg/xMg ratios equal to 1/9, 1/3, 1/1, and 3/1 for (Ag0.10Mg0.90)1-xPdx and (Ag0.25Mg0.75)1-xPdx at 1116 K and (Ag0.50Mg0.50)1-xPdx and (Ag0.75Mg0.25)1-xPdx at 1279 K and xMg/xPd ratios of 9/1 and 4/1 for (Mg0.90Pd0.10)1-xAgx and (Mg0.80Pd0.20)1-xAgx at 1116 K. Then, using the thermodynamic properties of the binary systems in the form of the Redlich-Kister equations and the changes in mixing enthalpies provided by this study, the ternary interaction parameters were determined with the Muggianu model and our own software (TerGexHm). Based on the binary and ternary interaction parameters, the partial mixing enthalpies of Ag, Mg, and Pd were calculated for the same cross-sections where the measurements were conducted. These studies were the first step of an investigation of the Ag-Mg-Pd system before the calculation of the phase diagram for this ternary system.